Technology and environment - Ausubel, Jesse; Sladovich, Hedy E. (National Academy Press, 1989)
Department heads from prestigious universities and high officials from major corporations contribute ten essays contending that environmental damage can best be repaired by the same technology that caused it. Annotation copyrighted by Book News, Inc., Portland, OR.